2019
DOI: 10.1088/1361-6560/ab33db
|View full text |Cite
|
Sign up to set email alerts
|

2D ultrasound imaging based intra-fraction respiratory motion tracking for abdominal radiation therapy using machine learning

Abstract: We have previously developed a robotic ultrasound imaging system for motion monitoring in abdominal radiation therapy. Owing to the slow speed of ultrasound image processing, our previous system could only track abdominal motions under breath-hold. To overcome this limitation, a novel 2D-based image processing method for tracking intra-fraction respiratory motion is proposed. Fifty-seven different anatomical features acquired from 27 sets of 2D ultrasound sequences were used in this study. Three 2D ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…In addition, the problem of real-time tracking is often solved by reducing the image fed to the tracking functions with the subsequent restoration of the original size [29], which is primarily caused by low performance, especially when processing HD images. This technology is not used for the experiment -the frames of the original size frames are examined since a hypothesis is put forward for testing the possibility of analyzing SD images by modern computing systems in real-time.…”
Section: Design and Methodsmentioning
confidence: 99%
“…In addition, the problem of real-time tracking is often solved by reducing the image fed to the tracking functions with the subsequent restoration of the original size [29], which is primarily caused by low performance, especially when processing HD images. This technology is not used for the experiment -the frames of the original size frames are examined since a hypothesis is put forward for testing the possibility of analyzing SD images by modern computing systems in real-time.…”
Section: Design and Methodsmentioning
confidence: 99%
“…A temporal consistency model was employed as a location prior and combined with the network-predicted location probability map for tracking the target in the ultrasound sequences. Huang et al developed a DL-based real-time motion tracking technique for ultrasound image-guided radiation therapy by combining the attention-aware fully CNN (FCNN) and the convolutional long short-term memory network (CLSTM) [113,114]. FCNN extracted spatial features while CLSTM refined the features via computing the saliency mask.…”
Section: B-mode Motion Trackingmentioning
confidence: 99%
“…As advances in deep learning algorithms, 40–47 convolutional neural network (CNN)‐based motion tracking methods have achieved initial promising results 48–55 . Nouri et al 48 .…”
Section: Introductionmentioning
confidence: 99%
“…As advances in deep learning algorithms, [40][41][42][43][44][45][46][47] convolutional neural network (CNN)-based motion tracking methods have achieved initial promising results. [48][49][50][51][52][53][54][55] Nouri et al 48 first reported a CNN-based algorithm to track landmarks in US image sequence by learning a distance metric of US images patches. To improve the accuracy and robustness of tracking, encoderdecoder networks, 54 recurrent neural network, 55 long short-term memory (LSTM) network, 49 and Siamese networks 50 have been introduced.…”
Section: Introductionmentioning
confidence: 99%